Peningkatkan Hasil Belajar Siswa melalui Strategi Contextual Teaching and Learning (CTL) pada Mata Pelajaran IPAS di Kelas IV Madrasah Ibtidaiyah Swasta Nurul Yaqin Simpang Sungai Duren - Agustin, Rini; Muhsinin, Umil; Putri, Fia Alifah (Lembaga Yasin AlSys, 2024)
This study examines how the Contextual Teaching and Learning paradigm might improve fourth-grade IPAS students' academic performance at MI Nurul Yaqin Simpang Sungai Duren. This study is a classroom action research (PTK) focused on the subject of IPAS concerning force material in the surrounding environment, employing CTL methodologies. The employed data gathering methods included the observation of student and instructor activities, test questions, documentation, and interviews. This PTK was conducted across two cycles, each comprising three meetings. The results of this study are 1) The results of observations of student learning activities and teacher teaching practices in Class IV MI Nurul Yaqin have increased. The outcomes of student learning activities in Cycle I were 57.61%, which climbed to 90.47% in Cycle II. Observations of teacher learning activities in Class IV MI Nurul Yaqin indicated a rise from 61% in Cycle I to 90% in Cycle II. The academic performance of grade IV pupils at MI Swasta Nurul Yaqin, originally below the standard, improved with the use of CTL approaches, achieving an average completeness rate of 59% in cycle I and 85.18% in cycle II. Fourth-graders at MI Nurul Yaqin Simpang Duren can improve their IPAS academic performance using CTL.